2382. Ceftolozane/Tazobactam for the Treatment of Multidrug-Resistant Pseudomonas aeruginosa Infections in Immunocompromised Patients: A Multi-Center Study. (26th November 2018) - Elabor, Abdulrahman; Molnar, Esther; King, Madeline; Gallagher, Jason; ,
Abstract: Background: Ceftolozane/tazobactam (TOL-TAZ) is a novel cephalosporin antibiotic combined with a known β-lactamase inhibitor. It has activity against some extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae and multidrug-resistant Pseudomonas aeruginosa (MDRPA). To date, little experience has been published on outcomes with TOL-TAZ for MDRPA infections in immunocompromised patients. Methods: This was a retrospective study of adult patients (≥18 years) with an immunocompromising condition (solid-organ transplant; hematologic malignancy; solid tumors; metastatic cancer) at 20 academic medical centers who had microbiologically confirmed MDRPA isolated in culture and received TOL-TAZ for at least 24 hours. 30-day survival, in-hospital mortality, and the rates of microbiologic and clinical cure were assessed. Results: Conclusion: In this study of 65 critically-ill immunocompromised patients, the 30-day survival was 86.1%; clinical cure was78.4% and microbiologic cure 75.3%. TOL-TAZ is a viable option for immunocompromised patients with MDRPA infections. Disclosures: J. Gallagher, Achaogen: Consultant, Consulting fee. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee and Research grant. Allergan: Consultant and Speaker's Bureau, Consulting fee. Astellas: Consultant and Speaker's Bureau, Consulting fee. Cempra: Consultant, Consulting fee. Cidara: Consultant, Consulting fee. CutisPharma: Consultant, Consulting fee. Paratek: Consultant, Consulting fee. Shionogi: Consultant, Consulting fee. Tetraphase: Consultant, Consulting fee. Theravance: Consultant, Consulting fee. The Medicines Company: Consultant, Consulting fee. Melinta: Speaker's Bureau, Consulting fee.